The Application of Human Comprehensive Development Theory and Deep Learning in Innovation Education in Higher Education - Jia-Lin Zhang (Frontiers in Psychology, 2020)
Since the core of talent training in modern society has changed from allowing students to master knowledge to adapting them to a lifelong learning society, this paper studied the innovation education in higher education by combining human comprehensive development theory and deep learning. First, this paper described the training needs of innovative education talents. Second, based on the human comprehensive development theory and deep learning, it puts forward views on innovative quality education in colleges and evaluates the students’ deep learning status by designing a deep learning evaluation model. From the perspective of students, a questionnaire for student-side use was designed according to the deep learning evaluation scale so that students could understand their deep learning status, make improvements based on their current situation, and improve the level of deep learning, thereby obtaining the inspiration of innovation education in higher education. The research shows that the students’ mastery of knowledge and skills is the highest, indicating that the mastery of students in this respect has reached the standard. Although the mean value obtained by the process and method is greater than the median, it is almost the same as the median, which indicates that the students’ mastery of the process and method is still lacking and further efforts are needed. In terms of psychology and values, the mean value is the lowest among the three dimensions and less than the median, indicating that students are the weakest in this respect and further improvement is required. In addition, a new teaching evaluation method was designed based on human comprehensive development theory and deep learning, contributing to innovation education in higher education in China.